Comparative phenolic, chromatic, and sensory composition of five monovarietal wines processed with microwave technology - L. Federico Casassa; Martin L. Fanzone; Santiago E. Sari (Heliyon, 2022)
The effect of MW technology (1,200 Watts for 10 min) on the chemical and sensory composition of five monovarietal wines with different phenolic composition was studied relative to untreated Control wines. MW improved polymeric pigment content by 30, 22 and 31% in Cabernet Sauvignon, Malbec, and Syrah wines, respectively, and anthocyanin extraction and non-tannin phenolics by 24% in Malbec and Syrah wines, respectively. In Nebbiolo and Pinot noir, MW had no effect on phenolics or chromatic characteristics. Anthocyanins in Nebbiolo wines were the lowest and their pigment profile was composed of 18% pyranoanthocyanins, but tannins were the highest, resulting in a tannin to anthocyanin ratio of 16. Pinot noir and Nebbiolo wines had comparable polymeric pigment content, despite dissimilar tannin to anthocyanin ratios, suggesting different mouthfeel characteristics in their respective wines. Conversely, wines of comparable tannin to anthocyanin produced wines of vastly different polymeric pigment content. MW-treated Cabernet Sauvignon wines showed an improved sensory profile.